Emotions and the tolerance of large carnivores: pumas in a crop-based landscape in Brazil. (25th June 2021) - Dechner, Andrea
Summary: Understanding the factors that affect the tolerance of carnivores is critical for proposing strategies for their conservation. A widely known hazard-acceptance model for large carnivores proposes that, unlike cognitive factors, emotional (affective) factors are secondary drivers of tolerance towards these species. The main objective of this article is to compare the effect of affective and cognitive factors on the tolerance of pumas ( Puma concolor ), using 109 semi-structured interviews conducted in a rural landscape in the state of Bahia (Brazil). Through the use of cumulative link models I found that although the cognitive model explained a considerable amount of variability (gen. R 2 = 0.38) in the tolerance of the species, the affective model explained a higher amount of variability (gen. R 2 = 0.44). In addition, an integrative model containing cognitive and affective factors explained the highest amount of variability (gen. R 2 = 0.51). Contrary to what has been believed for decades, humans may not process information regarding wildlife from a purely analytical viewpoint, and social-based strategies for carnivore conservation should benefit from integrative approaches that consider emotional responses to wildlife.